Energy Efficiency Optimization in Smart Buildings Using NodeMCU and Cloud Monitoring - Sandro Arnesto; Muhammad Rizqi Saputra; Sujiliani Heristian; Jordy Lasmana Putra; Musriatun Napiah; Rachmat Adi Purnama (Jurnal Infortech, 2026)
Inefficient energy management in modern building infrastructure is often caused by a lack of real-time visibility of power consumption and reliance on manual controls that are unresponsive to environmental dynamics. This study proposes the design of an integrated Internet of Things (IoT)-based Smart Building system for energy efficiency optimization. This system was developed using the NodeMCU ESP8266 microcontroller architecture, which orchestrates DHT11 and ACS712 sensors for the acquisition of precise data related to environmental parameters and electrical loads. The main contribution of this research lies in the implementation of a non-blocking programming algorithm to ensure stable sensor readings without interruption, as well as the application of a hysteresis control method in air conditioning (AC) units with thresholds of 30°C (ON) and 28°C (OFF). This hysteresis approach is designed to mitigate compressor short-cycling, which wastes energy. System testing shows that the integration of the RemoteXY mobile interface and OLED display is capable of presenting data telemetry with a response latency of less than 2 seconds. This system has proven effective in providing stable hybrid (automatic and manual) control, offering a low-cost but significant solution for reducing the operational energy consumption of buildings.